Impact of In-Service Training Programme on the TPACK of Science Teachers: A Case of New Juaben-North Municipality in the Eastern Region of Ghana - Charles Kwesi Koomson; Victoria Patterson; Ambrose Darku; Collins Owusu-Fordjour (EDUCATIO: Journal of Education)
This study assessed the impact that in-service training in selected Web 2.0 tools had on the performance of science teachers within the New-Juaben North Municipality of the Eastern Region of Ghana. The research adopted the case study design with a quantitative approach and was guided by two research questions. Twenty-five science teachers, drawn from some randomly selected senior high schools within the New-Juaben North municipality participated in this study. The questionnaire was used to collect data for analysis. The study found that in-service training in Web 2.0 tools had a strong positive impact on the TPACK of the science teachers and this had translated into improved performance of their students. It was recommended that more in-service training activities should be organised in diverse fields to enable teachers to acquire more skills to improve their teaching performance and hence students’ achievement.